(untitled) (Faridpur Medical College Journal, 2014)
This prospective observational study was carried out in the inpatient and outpatient department of surgery at Shaheed Ziaur Rahman Medical College Hospital, Bogra, during the period of 01.07.2008 to 31.12.2008 with a view to find out the incidence of breast carcinoma, fibroadenoma or other pathology in different age group. A total 130 patients with palpable breast lump were included in the study. Age of the patients was between 11 to 70 years. In most of the patients with breast lump Fine Needle Aspiration Cytology and biopsy were done. Sometimes ultrasonography, mammography and other routine investigations were also done. Among the study population 53.85% had benign lesions, Breast carcinoma accounted for 46.15% cases, fibroadenoma for 40.76% and fibroadenosis were in 10% cases. Fibroadenoma was common in second and third decade, while carcinoma of breast was common in third and fourth decade in this study. Here we attempted to find out the age incidence of breast lump and its correlation with clinical features, FNAC findings and histopathological report to improve the accuracy of diagnosis and management of breast disease. DOI: http://dx.doi.org/10.3329/fmcj.v8i2.20369 Faridpur Med. Coll. J. 2013;8(2): 56-58